The impact of an innovative web-based school nutrition intervention to increase fruits and vegetables and milk and alternatives in adolescents: a clustered randomized trial - Karine Chamberland; Marina Sanchez; Shirin Panahi; Véronique Provencher; Jocelyn Gagnon; Vicky Drapeau (BMC, 2017)
Abstract Background The increase in overweight and obesity in adolescents and its health-related consequences highlight the need to develop strategies, which could help them adopt healthy eating habits. The objective of this study was to evaluate the impact of an innovative web-based school nutrition intervention (Team Nutriathlon) aimed at promoting the consumption of vegetables and fruit (V/F) and milk and alternatives (M/A) in high school students and to identify facilitators and/or barriers influencing its success. Methods Ten classes of first and second year secondary students (grades 7 and 8) from the Québec City region were randomized into two groups (control n = 89 and intervention n = 193). Participants in the intervention (Team Nutriathlon) were to increase their consumption of V/F and M/A using an innovative web-based platform, developed for this study, over 6 weeks. The control group followed the regular school curriculum. The number of servings of V/F and M/A consumed by students per day was compared between the two groups before, during, immediately after and 10 weeks after the intervention using a web-based platform. Main outcome measures included V/F and M/A servings and facilitators and/or barriers of program success. Repeated measures linear fixed effects models were used to assess the impact of Team Nutriathlon on V/F and M/A consumption. A P-value of <0.05 was considered significant. Results Students in the intervention reported a significant increase of 3 servings and 1.8 servings per day of V/F and M/A, respectively, compared to the control group (P < 0.05); however, this was only observed in the short-term. Some factors contributing to the success of Team Nutriathlon included the team aspect of the program, use of the technology and recording results outside of classroom hours. Conclusion Team Nutriathlon represents an innovative web-based nutrition program which positively impacts V/F and M/A consumption among high school students. Using web-based or technological platforms may help youth adopt healthy eating habits that will have implications later in adulthood; however, further studies are needed to determine their long-term effects. Trial registration NCT03117374 (retrospectively registered).